Virtual reality approaches for enhancing postural stability and mobility in the elderly: A mini- review - Muhammad Ehab Azim; Sana Khalid; Muhammad Furqan Hassan; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2025)
The elderly population is growing rapidly, with asignificant portion facing challenges related to balanceand mobility. Importance of implementation of aneffectiveness fall prevention and balance trainingprogramme as an essential activity of daily living forelderly is still understated in national literature and policy.Conventional postural stability (PS) and mobility trainingprogrammes often face limitations in terms of provisionof adequate challenge, engagement and adherence.Virtual reality (VR) technology has emerged as apromising tool in healthcare, with potential applicationsin PS training for the elderly. VR based PS trainingprovides a fun and engaging environment resulting inenhanced motivation, with appropriate intensity andhigh frequency intervention. While individually designedVR systems are expensive; a range of commerciallyavailable full body motion platform based gamingsystems such as Nintendo Wii Fit, Xbox Kinect, PlayStationeyetoy etc. serve as potential and suitable alternatives.This review article provides a synthesis of currentevidence related to available systems, protocols andpotential limitations of individual systems with an aim toenhance utilization of VR based PS training fall preventionapproach to improve quality of life and healthy agingamong elderly. Keywords: Elderly, Fall Risk, Kinect, Postural StabilityTraining, Virtual Reality, Wii Fit.